Shirin Sabahi - Pocket folklore - Farzin, Media ca. 20./21.Jh; Fathi, Farnoosh 1981-; Galloway, David D. 1937-; Kleinman, Adam 1978-; Tolaas, Sissel 1961- (Edith-Russ-Haus für Medienkunst, 2019)
This book revolves around Matter and Mind, a sculpture by Japanese artist Noriyuki Haraguchi that was produced on-site at the Tehran Museum of Contemporary Art just before the museum's inauguration in 1977. Comprising a rectangular steel basin filled with used engine oil, the installation has remained in the building's atrium to this day and has become a symbol of the museum. Its central position in the building and reflective quality allude to the water pools of traditional Iranian architecture, while its material recalls crude oil, which essentially funded the new museum and its collection. The book appears as an epilogue to Shirin Sabahi's exhibition Borrowed Scenery at the Edith-Russ-Haus für Medienkunst, Oldenburg
This book appears as an epilogue to the exhibition "Shirin Sabahi: Borrowed Scenery" at Edith-Russ-Haus für Medienkunst, July 5 - September 30, 2018
Keywords: Sabahi, Shirin -- 1984-; Bildband; Ausstellungskatalog -- Edith-Russ-Haus für Medienkunst -- 05.07.2018-30.09.2018 -- Oldenburg